Predicting anatomical success and retinal restoration following macular hole surgery using optical coherence tomography parameters - Ece Ozal; Serhat Ermis; Cengiz Gul; Burakhan Kursat Aksoy; Murat Karapapak; Sadık Altan Ozal (BMC Ophthalmology)
Abstract Purpose To evaluate the prognostic significance of preoperative optical coherence tomography (OCT) parameters in predicting anatomical closure patterns following idiopathic macular hole (MH) surgery. Methods In this retrospective study, 61 eyes of 61 patients who underwent successful MH surgery were analyzed. Preoperatively, OCT-derived linear measurements and calculated indices, including the macular hole index (MHI), tractional hole index (THI), diameter hole index (DHI), hole form factor (HFF), and macular hole closure index (MHCI), as well as newly developed area-based indices such as the macular hole area index (MAI), macular hole tissue area index (MTAI), and macular hole cystoid space area index (MCSAI), were recorded. Anatomical closure was categorized into three types at the postoperative 6-month follow-up based on the integrity of the external limiting membrane (ELM) and ellipsoid zone (EZ): Type 1 (T1) (intact ELM and EZ), Type 2 (T2) (intact ELM and disrupted EZ), and Type 3 (T3) (disrupted ELM and EZ). Results Among closure types, statistically significant differences were observed in OCT parameters, particularly in MHI, THI, DHI, and HFF. T1 closures exhibited significantly higher MHI and HFF compared to T3 (p < 0.05). THI was significantly higher in T1 compared to T2 and T3 (p < 0.05). However, no significant correlations were found between visual acuity gain or postoperative BCVA at 6 months and any of the OCT indices evaluated. Conclusion Preoperative OCT parameters, specifically MHI, HFF, and THI, effectively predicted anatomical closure patterns following MH surgery. However, their prognostic value for visual acuity improvement was limited. The anatomical closure alone does not ensure favorable visual outcomes; therefore, evaluating the restoration of outer retinal layers (ELM and EZ) is crucial.